PERTUMBUHAN MISELIUM DAN PRODUKSI TUBUH BUAH JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DENGAN MEMANFAATKAN KULIT ARI BIJI KEDELAI SEBAGAI CAMPURAN PADA MEDIA TANAM - SUHARNOWO (LenteraBio: Berkala Ilmiah Biologi, 2012)
Epidermal of soya seed is very abundant but has not maximal utilized yet. One alternative that can be done is to utilize waste as additional media on the white oyster mushroom growing media. This research aim is to compare difference between mycelium growth and fruiting body production of Pleurotus ostreatus on different additional component media, and to get optimal percent combination of growing media. This research design is Completely Randomize Design (CRD) with 5 repetitions. The treatment on this research is bran and epidermal of soya seed with percent combination respectively: 80% : 20%, 50% : 50%, 20% : 80% and 100% epidermal of soya seed. This research parameter is mycelium growth and fruiting body production of Pleurotus ostreatus. This parameter is measured once tree day for 4 observation time. The data is analyzed by one way Anova with 5% significant level. The significant data will be continued by DMRT analysis. The result show that there is significantly different of mycelium growth Pleurotus ostreatus which be planted with different additional component on growing media combination. The growth average of mycelium on different percent of media combination between bran and epidermal of soya seed respectively 80% : 20%, 50% : 50%, 20% : 80% is 2,99 cm; 3,10 cm dan 2,86 cm. On the other result show that there is not significantly different of fruiting body prodution Pleurotus ostreatus which be planted with different additional component on growing media combination. This research suggest that epidermal of soya seed has a potential to substitute for bran and also is better compare with it as Pleurotus ostreatus growing media